Measuring the effects of climate techs and social inequality on climate performance using a SEM-DEA approach - Furlan, Marcelo [UNESP]; Mariano, Enzo Barberio [UNESP] (Routledge Journals, Taylor & Francis Ltd, 2022)
The objective of this study was to propose an index based on the IPAT model to quantify the performance of countries concerning their emissions, also taking into account the level of climate technology and the level of inequality. In this study, two quantitative techniques were applied to a sample of 100 countries and 21 indicators. The main results were: (a) a 1% increase in social inequality contributes to an increase in emissions levels by 0.105; (b) the 1% increase in climate techs contributes to reducing emissions levels by 0.141; (c) The proposed IPA index shows that only Estonia and Slovenia are the best performers, mainly in overcoming the inequality barrier, while South Africa and Nigeria are the worst performers in reducing their emissions. The results provide evidence that climate policies should contain social targets to improve country performance and should use a representative value to identify their effectiveness.
Keywords: data envelopment analysis; structural equation modeling; social inequality; IPAT model; climate change technologies; low carbon economy